Analysis of Chinese Students' Ability in the BIPA Program in Level B2 Semantic Interpretation through Tests - Irma Maharani; Novia Rahmadani; Elsa Meyrlinna; Azhara Nurizkya; Nia Budiana; Dany Ardhian (Universitas Nusantara PGRI Kediri, 2026)
This study aims to analyze the B2-level semantic comprehension abilities of Chinese students in the BIPA program. The focus of the study covers three main aspects, namely contextual meaning comprehension, semantic categorization abilities, and mastery of lexical relations such as synonyms, antonyms, hypernyms, and hyponyms. The method used is a descriptive qualitative approach with structured test instruments (17 questions) and in-depth interviews with participants. The results show that BIPA students at the B2 level are able to understand lexical meaning relations contextually, group words into appropriate semantic categories, and interpret inferential meanings based on clues in the discourse. However, a pattern of errors was also found that mainly originated from interference from the mother tongue (Mandarin) and limited exposure to authentic contextual input. (L1) This reinforces the view that semantic interference from the first language can lead to literal and inaccurate understanding, especially of figurative or idiomatic expressions. (L2) Qualitative data from interviews reinforce the finding that context-based learning strategies and interaction with native speakers play an important role in improving the depth of semantic comprehension. The pedagogical implications of this study emphasize the need to develop more contextual and integrative BIPA teaching materials and strategies in order to reduce semantic interference and support the achievement of higher communicative competence for Mandarin speakers (L1), as also emphasized by Pastini (2025) and Chen (2023) regarding the importance of integrating context and cross-cultural elements in language learning. (L2)